NSCA's Performance Training Journal (NSCAs Performance Training Journal, 2002)
Welcome to the debut of NSCA's Performance Training Journal. Since 1978, NSCA has been publishing the foremost journals for strength and conditioning professionals. In the interest of furthering our mission to "...support and disseminate research-based knowledge and its practical application ..." we have decided to make this electronic journal available to the public.